An Exploration of Teacher Power and its Place in Negotiation as a Teaching Strategy in Early Years - Helen Bernstone (New Zealand Journal of Teachers' Work)
A small scale case study research investigation evolved from an exploration of the beliefs held by early childhood teachers in relation to the balance of power in the teaching strategies they used. A strategy of negotiation supported the development of a model where instruction, co-construction and negotiation are connected to the problem solving states of dependence, interdependence and independence.